Prototype of Information System for Horticulture Pest and Disease Distribution - Susanti, Erni - (Informatika Pertanian, 2015)
The impact of climate change on the outbreak plant pest and disease seems to be likely increased in the future. However, operational information system on the outbreak of pest and disease on horticulture crops which can provide an overview of outbreak and distribution pest both in space and time is still very limited. The objective of the study is to developed prototype information system for providing information regarding area of horticulture pest and disease outbreak both space and time punctually and accurately. SIOPTHor is the early stage study to meet information regarding distribution of pest and disease outbreak. SIOPTHor is developed to performed information system including storage, processing, and analysis of distribution of pest and disease of horticulture data both in space and time on spatial and temporal. Distribution pest and disease attack data on horticulture crops (onions, red peppers and potatoes) for main horticulture crop areas in sub district level of Java were provided by local plant protection stations (BPTPH).. SIOPTHor was developed using waterfall systems development methods. This method consist of five stages, namely requirements analysis, design, implementation/coding, testing/verification and deployment/ maintenance. The software platform used for developing the system includes: 1) operation system Microsoft Windows 7, 2) programming language C#, 3) integrated development environment Microsoft Visual Studio 2008, 4) database management system Microsoft Access 2007, 5) mapper MapWinGIS v.3, 6) and software utilities such as Collapsible Panel, Microsoft Chart for NET, and adobe photoshop portable. The results showed SIOPTHor information system display informations including:1) analysis of pest and disease distribution both in space and time, 2) the Top-k OPT analysis in sub district level, 3) The most severe pest outbreak, and 4) analysis of pest and disease vulnerable index.